Do high-skill immigrants raise productivity? Evidence from Israeli manufacturing firms, 1990 - 1999 - Marco Daniele Paserman (Institute for the Study of Labor (IZA), 2008)
During the second part of the 1990s, the Israeli economy experienced a surge in labor productivity and total factor productivity, which was driven primarily by the manufacturing sector. This surge in productivity coincided with the full absorption and integration into the workforce of highly skilled immigrants from the former Soviet Union. The Soviet immigrants were disproportionately employed in manufacturing and, after an initial adjustment period, progressively moved into higher responsibility occupations where their skills could be put to use more efficiently. This has led some observers to comment that the high-skilled immigration wave was one of the main determinants for the fast growth of the Israeli economy in the 1990s. In this paper, I use a unique data set on Israeli manufacturing firms and investigate directly whether firms and industries with a higher concentration of immigrants experienced increases in productivity. The analysis shows that there is no correlation between immigrant concentration and productivity at the firm level in cross-sectional and pooled OLS regressions. First-differences estimates, which control for fixed unobserved differences between firms, reveal, if anything, a negative correlation between the change in output per worker and the change in the immigrant share. A more in-depth analysis reveals that the immigrant share was strongly negatively correlated with output and productivity in low-tech industries. In high-technology industries, the results tend to point to a positive relationship, hinting at complementarities between technology and the skilled immigrant workforce.
urn:nbn:de:101:1-2008070293
Keywords: J61; 330; Immigration; productivity; Internationale Wanderung; Internationale Arbeitsmobilität; Einwanderung; Qualifikation; Produktivität; Verarbeitendes Gewerbe; Israel